Comparison among parents of special needs and healthy children on their motivation and expectations of their child's proposed orthodontic treatment: a pilot study - Cheong, Joo Ming; Abu Bakar, Noraini (Ektodermal Displazi Grubu, 2022)
The purpose of this study was to compare parents’ motivations and expectations of special needs and healthy children on proposed orthodontic treatment. Questionnaires relating to pre-orthodontic treatment motivation and expectation were distributed to the parents of 21 special needs children (mean age = 11.76 ± 2.19) and mothers of 25 medically healthy children (mean age = 10.84 ± 1.21) from Sekolah Kebangsaan Indera Shahbandar (SKIS) in Pekan district, Pahang state of Malaysia. All children lived at home with their parents. Majority believed their child did not need orthodontic treatment (66.7% special needs; 68% healthy children) and that their child did not understand the purpose of treatment (61.9% special needs; 52% healthy children). 57.1% of parents were not prepared to help their special needs child with the orthodontic appliances care. Improving dental health was perceived as the main motivation for parents to seek orthodontic treatment for their child (81% special needs; 88% healthy children) besides enhancing aesthetic. 66.7% of parents expected that treatment could improve their special needs child’s quality of life, with 76.2% expected treatment may improve their child’s function in society, and 71.4% believed this would reflect positively on the parents’ own social acceptance. The result from this survey could provide insight for orthodontists on the potential uptake of orthodontic treatment by parents of special needs children and their expectations of the outcome of treatment.